Octreotide for the Management of Chylothorax in newborns, case report - Reza Saeidi; Shadi Nourizadeh (Mashhad University of Medical Sciences, 2015)
Chylothorax is the most common cause of pleural effusion in neonates. It is usually idiopathic. Neonatal chylothorax successfully respond to octreotide treatment and can reduce the duration of hospitalization. A number of therapeutic interventions have been used to reduce chyle production and promote resolution of a chylothorax. Initial management typically includes restriction or temporary cessation of enteral feedings. Enteral feedings high in medium-chain triglycerides (MCT) or parenteral nutrition may be used. These strategies alone are not successful in all patients. In the last several years, octreotide has become another option for management of patients with chylothorax. octreotide has a number of effects on the gastrointestinal system, including a decrease in splanchnic blood flow and inhibition of serotonin, gastrin, vasoactive intestinal peptide, secretin, motilin, and pancreatic polypeptide. We report an infant who had spontaneous chylothorax with patent ductus arteriosus that was managed primarily as congenital heart disease. Our case was treated successfully with octreotide without the need to insertion of chest tube.